2014
DOI: 10.1111/exd.12392
|View full text |Cite
|
Sign up to set email alerts
|

The possible involvement of skin dryness on alterations of the dermal matrix

Abstract: Moisturization of the skin plays an important role in maintaining skin homeostasis. Although it is understood that skin dryness initiates the formation of fine wrinkles, there are few objective reports to support that understanding. The purpose of this study was to establish an in vitro dry epidermal model using reconstructed human epidermal equivalents (RHEEs) and to elucidate the relationship between skin dryness and alterations of the dermal matrix which is one of the causes for the formation of wrinkles. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…In order to investigate the influence of skin dryness on the development of sensitive skin, we established a dry skin model prepared by exposing the surface of RHEEs to dry air . In the dry skin model, we observed significantly increased secretion of IL‐1α and NGF, and up‐regulated expression levels of NGF and MMP‐9 mRNAs (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to investigate the influence of skin dryness on the development of sensitive skin, we established a dry skin model prepared by exposing the surface of RHEEs to dry air . In the dry skin model, we observed significantly increased secretion of IL‐1α and NGF, and up‐regulated expression levels of NGF and MMP‐9 mRNAs (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that IL‐1α is secreted at high levels in dry skin. In fact, it was found that the secretion of IL‐1α is increased in an artificial dry skin model . Also, IL‐1α is a proinflammatory cytokine and stimulates ROS synthesis through the activation of IL‐1 receptor‐associated kinase‐1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That concept is supported by the results of a dry skin model of a reconstructed human epidermal equivalent exposed to dry conditions. That dry skin model showed a higher level of IL‐1α secretion and resulted in higher CP levels than in the control, because IL‐1α generates ROS through the activation of NADPH oxidase by signaling of interleukin‐1 receptor‐associated kinase‐1 . These facts indicate the possibility of accelerating the turnover rate and accumulating CPs in dry skin, such as Groups III and/or IV, as follows: ROS accelerates the turnover rate by causing a faint inflammation in the skin and accumulates CPs by the oxidation of proteins through lipid peroxidation, which is the initiation reaction of protein carbonylation …”
Section: Discussionmentioning
confidence: 92%
“…Galectin‐1 mRNA expression in normal keratinocytes was gradually suppressed with cell growth to reach confluency, suggesting the possible involvement of galectin‐1 in keratinocyte differentiation. In a study of in vitro dry epidermal model using reconstructed human epidermal equivalents (RHEE), galectin‐1 was detected in conditioned medium from RHEEs cultured under dry conditions . The functional role of galectin‐1 in keratinocyte differentiation and skin moisturization requires further exploration.…”
Section: Keratinocyte Differentiation and Skin Barrier Functionmentioning
confidence: 99%